Pemberdayaan Masyarakat Melalui Sosialisasi Sebagai Upaya Penanggulangan Stunting Di Desa Mentor, Kecamatan Sumberasih, Kabupaten Probolinggo - Muhammad Agus Muljanto; Balqista Safia Haya; Hanin Kaulika Ulma; Adhitya Novrizal Firmanda (Cv. Utility Project Solution, 2023)
Stunting is a problem that often affects children aged 0-12 years. One of the ways to overcome the high stunting rate in Mentor Village, Sumberasih District, Probolinggo is through community empowerment by holding socialization on Clean and Healthy Behavior conducted at SDN Mentor 1 and socialization on Provision of Supplementary Food at posyandu. Socialization of Clean and Healthy Behavior (CLBH) was held with the aim of providing students with understanding and knowledge about the importance of maintaining cleanliness and health. While the socialization of Supplementary Feeding aims to provide an understanding of menus that are suitable for infants and toddlers. The target of the socialization of Clean and Healthy Behavior (CLBH) is Mentor 1 Elementary School students, while the Provision of Supplementary Food socialization is posyandu participants. The method of implementation through four stages, namely observation, planning, socialization and evaluation. The technique used for data collection is by using a questionnaire. The results of these activities can be seen that the knowledge of students related to CLBH before the socialization was held was 45% and had increased to 89%. Socialization of Supplemental Feeding by taking 20 respondents, it was shown that the mothers of toddlers had paid attention to and maintained the provision of food to infants and toddlers, which showed that 70% of the participating mothers paid attention to variations of the Supplemental Feeding menu for infants and toddlers.